Unraveling the Mechanism and Regioselectivity of the B12‐Dependent Reductive Dehalogenase PceA. Issue 35 (26th July 2016) - Liao, Rong‐Zhen; Chen, Shi‐Lu; Siegbahn, Per E. M.
Abstract: PceA is a cobalamin‐dependent reductive dehalogenase that catalyzes the dechlorination of perchloroethylene to trichloroethylene and then to cis ‐dichloroethylene as the sole final product. The reaction mechanism and the regioselectivity of this enzyme are investigated by using density functional calculations. Four different substrates, namely, perchloroethylene, trichloroethylene, cis ‐dichloroethylene, and chlorotheylene, have been considered and were found to follow the same reaction mechanism pattern. The reaction starts with the reduction of Co II to Co I through a proton‐coupled electron transfer process, with the proton delivered to a Tyr246 anion. This is followed by concerted C−Cl bond heterolytic cleavage and proton transfer from Tyr246 to the substrate carbon atom, generating a Co III −Cl intermediate. Subsequently, a one‐electron transfer leads to the formation of the Co II −Cl product, from which the chloride and the dehalogenated product can be released from the active site. The substrate reactivity follows the trend perchloroethylene>trichloroethylene≫ cis ‐dichloroethylene≫chlorotheylene. The barriers for the latter two substrates are significantly higher compared with those for perchloroethylene and trichloroethylene, implying that PceA does not catalyze their degradation. In addition, the formation of cis ‐dichloroethylene has a lower barrier by 3.8 kcal mol −1 than the formation of trans ‐dichloroethylene and 1, 1‐dichloroethylene, reproducing the regioselectivity. These results agree quite well with the experimental findings, which show cis ‐dichloroethylene as the sole product in the PceA‐catalyzed dechlorination of perchloethylene and trichloroethylene. Abstract : DFT calculations were used to understand the mechanism and regioselectivity for the cobalamin‐dependent reductive dehalogenase PceA (see scheme). The Co I state initiates the heterolytic C−Cl bond cleavage in concomitant with the protonation of the substrate carbon atom. cis ‐Dichloroethylene was found to be the sole product in the dechlorination of trichloroethylene, which is in good agreement with the experimental finding.